Social-Environmental Perception of Artisanal Fishermen bout Climate Change, Its Impacts on Fishing: A Comparison Between Socio-Spatially Segregated Communities - Rodrigues, Jéssica Garcia; de Freitas, Débora Martins [UNESP]; Woltrich, Ana Emília; Machado, Ingrid Cabral (Springer Nature, 2024)
Based on the hypothesis that the socio-spatial pattern can influence the perception of socio-environmental phenomena, this study aimed to investigate the environmental perception of two communities of artisanal fishermen in Baixada Santista, on the coast of São Paulo, about climate change and its relationship with their socio-spatial distribution pattern. We applied semi-structured interviews that addressed social and spatial aspects to understand whether socio-spatial segregation influences the perception of fishermen from the communities of Perequê (Guarujá–São Paulo) and Monte Cabrão (Santos-SP). We used the content analysis method in order to identify the key points of the stakeholder’s perception. The results obtained indicated that the socio-spatial segregation of communities has an influence on the way in which fishermen perceive changes in the environment. The more socio-spatially segregated community was demonstrated to perceive less frequently and fewer impacts arising from climate changes in comparison to the less segregated community, which is more inserted in an urban context. Therefore, popular knowledge may contribute to the pluralization of scientific research, adding other values in decision-making public policies at the socio-environmental governance level. This can be possible through the analysis of the natural resources by its local users whose environmental perception is clearly relevant to Western science.
Keywords: Artisanal fishing; Coastal zone; Local knowledge; Socio-spatial segregation